MANAJEMEN KURIKULUM KITAB KUNING DI PONDOK PESANTREN - Ihsan, Zainul; Muali, Chusnul (Managere: Indonesian Journal of Educational Management, 2020)
This paper aims to explore the concept of curriculum management implementation in the learning of the kitab kuning at Islamic boarding schools. Through good and correct management of kitab kuning learning, it is expected that kitab kuning learning outcomes can be achieved optimally. This research uses a qualitative approach to the type of library research. The data analysis technique uses content analysis. The results showed that the management of the kitab kuning curriculum in pesantren was carried out in an integrated manner, because the integrated curriculum had a learning approach that allowed students, both individually and in groups to actively search, explore, and find concepts. Not to forget this integrated curriculum is a new curriculum without leaving the previous curriculum model, so that the integration of the old and new curriculum models can strengthen pesantren education as a unique, creative, and unique institution.